The secrets we bury - Webb, Debra (Mira, 2019)
Doctor Rowan Dupont knows death. She grew up surrounded by it in her family<U+2019>s Victorian funeral home, and it<U+2019>s haunted her since the day her twin sister drowned years ago. Between her mother<U+2019>s subsequent suicide and the recent murder of her father, coming home to run the funeral home feels fitting<U+2014>even if it leaves her vulnerable to an obsessive serial killer. Rowan refuses to let fear keep her from honoring her family. But the more time she spends back in Winchester, Tennessee, the more she finds herself questioning what really happened that fateful summer. Had her sister<U+2019>s death truly been an accident? And what pushed their mother to take her own life? The dark lake surrounding Rowan<U+2019>s hometown holds as many secrets as the bodies that float in its chilling depths. But Rowan is running out of time if she<U+2019>s going to uncover the truth before somebody sinks her for good.